Development of Quality Standards of Corylus colurna (Linn.) Fruit - 2, H.Hasan2, B.Ali2, N.Chaudhary2, M.Khan2, A.Ali2, S.Najib2, H.Farooqi3,H.N.Khan2*, P.Akhtar1, M.Ali2, M.P.Sharma4, Md.Waris (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">Corylus colurna<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> (Linn.) belonging to family Betulaceae is a deciduous tree distributed throughout the western temperate region of Himalayas in India. It is very valuable traditional herbal medicine. In present investigation an attempt has been made for the pharmacognostical standardization and evaluation of C. colurna fruit. The pharmacognostical evaluation comprises of detailed macroscopy, powdered microscopy, fluorescence analysis and physical constants such as ash and extractive values. The fruit extracts were subjected to preliminary phytochemical screening. The data obtained in present study will serve as valuable tool for identification, authentication and detection of adulterants, standardization and quality control of the drug. The developed technique will also be useful for the standardization of formulations containing C. colurna.